Broadband and Low-Profile H-Plane Ridged Horn Antenna - Chen, Zhuozhu (2016)
This paper presents a broadband and low-profile Hplane horn antenna mounted on a large ground plane. By employing stepped ridges and an ellipse-shaped copper taper extended along the horn aperture, the proposed antenna achieves a wide bandwidth from 4.2 GHz to 18 GHz for VSWR 2 while retaining the antenna height of only 5.508mm. Acceptable gain values with nearly end-fire radiation beams are obtained over the entire frequency band.